Women and Men in Arsi Oromo Proverbs: an Implication for Gender Equality - Ayehu Bacha; Lenin Kuto (Universitas Islam Negeri Imam Bonjol Padang, 2019)
This article is aimed at investigating how men and women are portrayed in Arsi Oromo proverbs. To do this, proverbs are placed in their wider cultural context and philosophical outlook of the people. To this end, interview, focus group discussion and document analysis were used as a method of data collection to generate data on the topic under discussion. Contextual approach was exploited to analyze and synthesize raw data. Multifaceted nature and functions of proverbs are thoroughly discussed in the lens of cultural context. Thus, the finding of this research unveiled that there are many proverbs portraying both sexes positively and negatively when seen superficially. However, this research has concluded that (1) it is impossible to wrap up whether women are subordinate or not and men are dominant in Oromo culture by selecting proverbs in which women and men are directly or indirectly mentioned, (2) the philosophical outlook of the Oromo does not support the claim that proverbs are weapon for women’ inferiority and (3) proverbs which seem contradictory to each other are complementary and cannot give an insightful picture about gender philosophy of the society if detached from worldview of the society. Thus, proverbs should be placed in the worldview of the society from which they are flourished and their many edged functions/natures should be taken in to consideration.